2017
DOI: 10.5935/1518-0557.20170048
|View full text |Cite
|
Sign up to set email alerts
|

Fresh embryos versus freeze-all embryos - transfer strategies: Nuances of a meta-analysis

Abstract: ObjectiveThe present meta-analysis aimed to evaluate whether the freeze-all strategy (Freeze/All-ET) could bring about improvements in the clinical assisted reproductive technique (ART) outcomes when compared with the fresh embryo transfer strategy (Fresh-ET) in patients undergoing an ART cycle in accordance with the mean number of oocytes collected.MethodsA systematic review based on electronic searches in databases (PubMed, EMBASE, Web of Science, SCOPUS, and Cochrane Central Register of Controlled Trials) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 40 publications
(70 reference statements)
0
25
0
Order By: Relevance
“…Independent of PGD, the IVF world generally has seen improvement in embryo cryopreservation techniques which later impacted the world of PGT-A. Indeed, in recent years, there has been a move in the direction of embryo cryopreservation with a view to a later transfer (freeze-all) strategy in an unstimulated cycle (Dieamant et al 2017). Thus, while increased pregnancy success rates have been attributed to the advancement of PGT-A technologies (improved blastocyst biopsy (previous section) and aCGH, NGSsee next sections), some argue that credit may possibly be given to an improvement associated with frozen embryo transfer (Dieamant et al 2017).…”
Section: Impact Of Vitrification and Freeze-all Strategies On The Chomentioning
confidence: 99%
See 2 more Smart Citations
“…Independent of PGD, the IVF world generally has seen improvement in embryo cryopreservation techniques which later impacted the world of PGT-A. Indeed, in recent years, there has been a move in the direction of embryo cryopreservation with a view to a later transfer (freeze-all) strategy in an unstimulated cycle (Dieamant et al 2017). Thus, while increased pregnancy success rates have been attributed to the advancement of PGT-A technologies (improved blastocyst biopsy (previous section) and aCGH, NGSsee next sections), some argue that credit may possibly be given to an improvement associated with frozen embryo transfer (Dieamant et al 2017).…”
Section: Impact Of Vitrification and Freeze-all Strategies On The Chomentioning
confidence: 99%
“…Indeed, in recent years, there has been a move in the direction of embryo cryopreservation with a view to a later transfer (freeze-all) strategy in an unstimulated cycle (Dieamant et al 2017). Thus, while increased pregnancy success rates have been attributed to the advancement of PGT-A technologies (improved blastocyst biopsy (previous section) and aCGH, NGSsee next sections), some argue that credit may possibly be given to an improvement associated with frozen embryo transfer (Dieamant et al 2017). Transfer of vitrifiedwarmed single blastocysts yields improved outcomes (Roy et al 2014) and higher live birth rates (77% vs 59%) in the frozen group compared with the fresh group (Coates et al 2017), which could be attributed to a better preparation of endometrium in the next cycle avoiding the possible detrimental effect of ovarian hyperstimulation on endometrial receptivity.…”
Section: Impact Of Vitrification and Freeze-all Strategies On The Chomentioning
confidence: 99%
See 1 more Smart Citation
“…14 Therefore, many studies have been reported showing reduced time of the cryopreservation procedure, aiming to eliminate the high costs with equipment and also to improve the quality of frozen and thawed embryos in order to promote good results in the pregnancy rate. 8,11,15 One way to achieve these goals was through the use of vitrification techniques, which, other than slow freezing, requires a radical increase in both the concentration of the cryoprotectants and the rate of cooling. 16,17 Current procedures describe that the exposure of the suspended cells in a small volume of cryoprotectants in high concentration, for a short period of time and placed at low temperature directly on nitrogen liquid at -196 ° C does not allow the formation of ice crystals.…”
Section: /7mentioning
confidence: 99%
“…[5][6][7] Emphasizing the importance of the TEC, there are many reports that a stimulation in the treatment of IVF and the exposure of women submitted to high hormone levels may alter endometrial receptivity. 8…”
Section: Introductionmentioning
confidence: 99%